Meteorological data from Šibenik, Croatia, August 2020 - Ribas-Ribas, Mariana; López-Puertas, Ander; Wurl, Oliver; Frka, Sanja (In: Ribas-Ribas, M et al. (2025): Diel variability of thermohaline and carbon system parameters in the sea-surface microlayer and underlying water of a Mediterranean coastal site (Šibenik, Croatia) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984017, 2025)
Meteorological data recorded every 5 minutes during the August 2020 Šibenik campaign. Measurements were taken with an on-site weather station located near the sampling area.
Keywords: Adriatic Sea; air-sea exchange; CO2 fluxes; coastal biogeochemistry; diel variability; diurnal cycle; Marine Carbonate System; sea-surface microlayer; underlying water